2012
DOI: 10.1590/s1517-83822012000200015
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of Staphylococcus aureus and escherichia coli strains by neutralizing IgY antibodies from ostrich egg yolk

Abstract: Ostrich raising around the world have some key factors and farming profit depend largely on information and ability of farmers to rear these animals. Non fertilized eggs from ostriches are discharged in the reproduction season. Staphylococcus aureus and Escherichia coli are microorganisms involved in animal and human diseases. In order to optimize the use of sub products of ostrich raising, non fertilized eggs of four selected birds were utilized for development of polyclonal IgY antibodies. The birds were imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
1
4
0
1
Order By: Relevance
“…The determination of antimicrobial activities of either experimented IgY or probiotic (500 µl each) and a mixture of both (250 µl each) in vitro revealed that IgY can also retain a bactericidal activity against gram-positive bacteria including S. aureus and L. monocytogenes at a concentration of 1,500 µg/ml. These findings coincided with a previous report that showed an effective bactericidal activity of IgY against S. aureus growth, suggesting the therapeutic benefits of IgY (33). This result was also consistent with a previous study (34) that showed the ability of IgY to suppress Staphylococcus in chicken meat.…”
Section: Discussionsupporting
confidence: 93%
“…The determination of antimicrobial activities of either experimented IgY or probiotic (500 µl each) and a mixture of both (250 µl each) in vitro revealed that IgY can also retain a bactericidal activity against gram-positive bacteria including S. aureus and L. monocytogenes at a concentration of 1,500 µg/ml. These findings coincided with a previous report that showed an effective bactericidal activity of IgY against S. aureus growth, suggesting the therapeutic benefits of IgY (33). This result was also consistent with a previous study (34) that showed the ability of IgY to suppress Staphylococcus in chicken meat.…”
Section: Discussionsupporting
confidence: 93%
“…Ostrich and quail immunoglobulins Y were characterized in terms of their molecular weight (SDS-PAGE and western-blotting) and their ability to recognize and bind to a commercially available horseradish peroxidase (HRP)-labeled rabbit anti-hen IgY antibody in an ELISA system[ 120 ]. As revealed, the ostrich IgYs could be hardly recognized by the HRP-labeled anti-hen antibody we used, though other researchers reported successful use of commercially available secondary anti-hen antibodies to assess the immunochemical efficiency of specific ostrich IgYs[ 121 ]. On the other hand, HRP-labeled secondary anti-ostrich-IgY antibodies have been specially developed and used to evaluate ostrich IgYs with ELISA[ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibiting growth activity of IgY anti-Streptococcus mitis was preserved by extracting yolk antibodies by precipitation with PEG 6000 and AmS and further isolation by DEAE cellulose ion exchange column chromatography [34]. Similarly, growth inhibition of Staphylococcus aureus and Escherichia coli was obtained with yolk antibodies isolated by NaS and AmS precipitations [35].…”
Section: Isolating Igy By Precipitation Methodsmentioning
confidence: 99%